In-plane behaviour of grouted concrete masonry under biaxial states of stress - Khattab, Mohamed Samir Magdy (My University, 1993)
The available literature on the in-plane behaviour of masonry was categorized and reviewed under one of three research approaches; experimental testing of masonry shear walls, microscopic modelling, and macroscopic modelling. The significant differences found in the results obtained from different research programs may leave a wrong impression about the potential of masonry as a structural material. The literature review also pointed out the lack of experimental data on the macro-behaviour of grouted concrete masonry, particularly for reinforced assemblages. Accordingly, the reported investigation provides explanations of behaviours which lead to an improved understanding of the in-plane behaviour of grouted concrete masonry. The experimental part provides a body of test data for North American conditions (practice and material) to form the basis of a macro-behaviour model. The experimental program in this investigation included two major parts; biaxial tests and auxiliary tests. The biaxial tests involved a total of 36 full scale unreinforced or reinforced panels tested under uniform states of biaxial tension-compression. A biaxial test rig was specially devised to perform these tests. The variables considered covered the bed joint orientation θ, the ratio between principal stresses σ₁/σ₂, and the percentages of reinforcement used parallel and normal to the bed joints. The auxiliary tests comprised 33 prisms tested under uniaxial compression, 27 prisms tested under uniaxial tension, and 15 couples tested under direct shear. In addition, a large number of component material tests were performed to determine the physical and mechanical properties of each material used. These also served as control tests. A macro-model was proposed to predict the in-plane behaviour of grouted concrete masonry. In this model, the masonry assemblage was replaced by an "equivalent material" which consisted of a homogenous medium intersected by two sets of planes of weakness (along the head joint and bed joint planes) and two sets of reinforcement. The macro-behaviour of the "equivalent material" was determined by smearing the influence of these sets, which provided a means for modelling the inherent part of the anisotropic characteristics of masonry assemblages. On the other hand, the behaviour of the homogeneous medium was described by an orthotropic model to account for the induced part of the anisotropic characteristics. The reliability of the proposed model was confirmed using the experimental results from this investigation and others. The model was also used to fill the gaps in the available test results and to provide a more complete picture of the in-plane behaviour of grouted masonry.
Keywords: Civil Engineering; Engineering Mechanics; Civil Engineering